THE EFFECT OF STORY IMPRESSION STRATEGY TOWARD READING COMPREHENSION OF NARRATIVE TEXT AT SECOND YEAR STUDENTS AT SMA MUHAMMADIYAH RAMBAH - Merli, Rina; Rasyidah, Ummi; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purposes of this research were to find out studentsâ reading comprehension on narrative text taught byusing Story Impression strategy and taught without using Story Impression strategy and to find out whetherthere was a significant effect of using Story Impression strategy toward reading comprehension of narrative textat the second year students at SMA Muhammadiyah Rambah. This research was an experimental research, thedesign of research was pre-test â post-test. The result of this research in post-test experimental group 22students got 95.7% ( good to excellent ). While in post-test control group 3 students got 11.5% ( good toexcellent ).